Pemberdayaan Ekonomi Masyarakat Melalui Edukasi Investasi Di Pasar Modal Sesuai Fatwa Mui No. 80 Bagi Pengurus Masjid Kota Depok - Warsini, Sabar; Masjono, Ali; Seno, Petrus Hari Kuncoro; Nuraeni, Fatimah; Aminah, Indianik (Unit Penelitian dan Pengabdian kepada Masyarakat (UP2M) Politeknik Negeri Jakarta, 2020)
Fatwa of Majelis Ulama Indonesia No 80/DSN-MUI/III/2011 about sharia capital market, should be told to the general public that society understand about sharia investment. Galery Investasi PNJ have significant roles in educate people that understand why investment in accordance sharia truth and Islamic.Program study of D4 Financial Management PNJ have competence in the field of capital market, have an obligation to do an activity education about sharia investment through the Community Social Activity to the mosque management in Depok City. Objectives of the Community Social Activity is to increase community understanding about the truth and the importance of investment in accordance with the islamic sharia so that community can be avoided from fraud investment. Method is carried out by providing lectures education by expert sharia capital market do accompanied by a trading use application MNC-trade. This Community Social Activity done in cooperation with MUI Depok